ASPERGILLUS FUMIGATUS IN COMMERCIAL POULTRY FLOCKS, A SERIOUS THREAT TO POULTRY INDUSTRY IN PAKISTAN - M. A. Sajid; I. A. Khan; U. Rauf (Journal of Animal and Plant Sciences, 2006)
The present study was carried out to determine the incidence of Aspergillus fumigatus in commercial poultry flocks. Aspergillus fumigatus was isolated from the lungs and air sacs of affected birds. Sixty four suspected cases of fungal infection were used in the study. Thirty one cases were found positive for Aspergillus fumigatus by culturing. Gross lesions were observed in lungs, trachea and thoracic air sacs at postmortem examination. Small white nodular lesions 1 millimeter diameter were observed in the congested lungs and thoracic air sacs. Branched septate hyphae were observed under oil emersion. Aspergillus fumigatus was cultured on sabouraud agar. Velvety white colonies were seen, at first, which turned dark green to grayish later. It was observed that disease was significantly (P<0.005) higher in hot and humid season. The disease was significantly (P<0.000) higher in birds of less than two weeks age. It was also found that incidence of Aspergillus fumigatus was considerably high in flocks reared on sawdust litter as compared to rice husk litter.
Keywords: Aspergillosis; incidence; season; litter; saprophyte.